The Bald Ibis From Eagle Understanding A Historical City From The Traditional Craftmanship Language - Kasapoglu, Aytul (Advances in Social Sciences Research Journal, 2020)
The name and purpose of this work was inspired by the fact C.Wright Mills (1959) described sociology as an “Intellectual Craftsmanship” . The main aim is to examine traditional craft figurations (Elias, 1939; 2000) in a historical city (Mugla), which I find appropriate to explain with workshop metaphor. Paul Thompson (1978), when he says to hear the voice of the past, underlines the importance of the bottom up historical approach, ordinary people and everyday events in the construction of a more democratic and egalitarian future. In this study, it was paid attention to the changes in both time and space to be treated in a process and holistic manner by rejecting “essentialism ” and “dualities”. In this study, it has been tried to make appropriate analyses by using the biographical narratives formed by the oral history technique. The originality of this research, based on the theoretical approach of Relational Sociology, is also here.